2004
DOI: 10.1117/1.1628242
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive determination of the optical properties of adult brain: near-infrared spectroscopy approach

Abstract: Abstract. The basic parameters for physiological measurements provided by near-infrared spectroscopy are the local absorption and scattering coefficients. For the adult human head, they have been difficult to measure noninvasively because of the layered structure of the head. The results of measurements of absorption and reduced scattering coefficients through the forehead on 30 adult volunteers using a multidistance frequency domain method are reported. The optode separation distance ranged from 10 to 80 mm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
151
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(168 citation statements)
references
References 17 publications
13
151
0
4
Order By: Relevance
“…The original MD NIRI approach was extended to two-layer models (Choi et al, 2004;Fabbri et al, 2004) and ultimately to five-layer models (Yamada et al, 2009(Yamada et al, , 2010, the last one including also ÎŒ s â€Č changes in the modeling. Concerning the limitations of the method, Franceschini et al (1998) showed using a MD NIRI approach based on a two-layer model that absorption changes in the lower layer can be correctly determined when the layer thickness is less than~0.6 cm.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
“…The original MD NIRI approach was extended to two-layer models (Choi et al, 2004;Fabbri et al, 2004) and ultimately to five-layer models (Yamada et al, 2009(Yamada et al, , 2010, the last one including also ÎŒ s â€Č changes in the modeling. Concerning the limitations of the method, Franceschini et al (1998) showed using a MD NIRI approach based on a two-layer model that absorption changes in the lower layer can be correctly determined when the layer thickness is less than~0.6 cm.…”
Section: Multivariate Methods Of Typementioning
confidence: 99%
“…Few studies focus on in vivo optical properties [21][22][23], but the data presented are preliminary, or limited to few subjects, or obtained after approximations (e.g. the head was modelled as homogeneous medium).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in light attenuation recovered from this modeling can be converted to ICG concentration and deconvolved to yield CBF . In a similar way, when a frequency-modulated light signal is introduced into a tissue, the amplitude and phase components of the detected light depend on the tissue geometry and optical properties (Choi et al, 2004). In theory, the same time-of-flight information collected using time-resolved NIRS is contained in frequency-domain measurements.…”
Section: Extra-cerebral Signal Contaminationmentioning
confidence: 98%